IQ and digital inequality: An empirical investigation - van Deursen, Alexander JAM; van Dijk, Jan AGM (New media & society, 2023)
Cognitive intelligence is rarely discussed in the context of digital inequality for practical and normative reasons: substantial difficulties around measurements and the fact that it cannot (easily) be changed. In the current contribution, cognitive intelligence is studied in relation to resources and appropriation theory which explains digital inequality as a process of four successive phases of Internet access: motivational, material, skills, and usage. For the measurement of cognitive intelligence, we build on considerable efforts devoted to developing alternatives to cumbersome intelligence quotient (IQ) tests of intelligence. We conducted a two-wave online survey in the Netherlands, resulting in a sample of 1733 respondents. The importance of IQ was confirmed with direct positive effects on education, economic, social, and cultural resources, and on Internet attitude and skills. The results reveal several details that can enhance our understanding of the specific mechanisms through which IQ and education operate in digital inequalities.